Experimental study for determining the diameter of plasma channel and energy distribution ratio into workpiece during WEDM process of AISI 316 - Warregh, Adel S.O.; Zahiruddin M. Md. Zain, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Electrodes removal phenomena of WEDM is important to understand the efficiency and the process accuracy. To clarify and understand the phenomenon, the plasma channel diameter and distribution of energy into electrodes are required. However, reports on the distribution of energy and plasma channel diameter are scarce. In this work, the energy distribution and plasma diameter of WEDM process were obtained. By comparing the melted material boundary in the crater obtained by the metallographic approach with the curve isothermal of the thermo-physical model obtained by finite element modelling (FEM), the distribution of energy besides that diameter of the plasma channel of the WEDM process were estimated. From this study, results indicate that the expansion of the diameter of the plasma channel must be taken into consideration in order to be more consistent with the real WEDM process. By applying the proposed method in this study, the distribution of energy and diameter of plasma channel, in various dielectrics with different polarities were investigated. However, by comparing the findings of the current study with the previous works, it turns out that the distribution of energy into the workpiece and the diameter of the plasma channel may be calculated by this approach.